Photodissociation dynamics of the diamondoid adamantane induced by attosecond XUV pulses. Issue 15 (January 2020) - Maclot, S; Peschel, J; Lahl, J; Wikmark, H; Rudwaski, P; Coudert-Alteirac, H; Rousseau, P; Indrajith, S; Huber, B A; Díaz-Tendero, S; Johnsson, P
Synopsis: Adamantane is the simplest of the diamondoid molecules, which due to their high stability are of high interest both in astrophysics and nanotechnology. This work investigates the molecular photodissociation after ionization by attosecond XUV pulses. The fragmentation dynamics is inferred by means of velocity map imaging spectrometry, covariance analysis techniques and quantum chemistry calculations.